Updated parameter estimates for GW190425 using astrophysical arguments and implications for the electromagnetic counterpart. Issue 1 (14th March 2020) - Foley, Ryan J; Coulter, David A; Kilpatrick, Charles D; Piro, Anthony L; Ramirez-Ruiz, Enrico; Schwab, Josiah
ABSTRACT: The progenitor system of the compact binary merger GW190425 had a total mass of 3.4^+0.3_-0.1 M⊙ (90th-percentile confidence region) as measured from its gravitational wave signal. This mass is significantly different from the Milky Way (MW) population of binary neutron stars (BNSs) that are expected to merge in a Hubble time and from that of the first BNS merger, GW170817. Here, we explore the expected electromagnetic (EM) signatures of such a system. We make several astrophysically motivated assumptions to further constrain the parameters of GW190425. By simply assuming that both components were NSs, we reduce the possible component masses significantly, finding m_1=1.85^+0.27_-0.19 M⊙ and m_2=1.47^+0.16_-0.18 M⊙ . However, if the GW190425 progenitor system was an NS–black hole (BH) merger, we find best-fitting parameters m_1=2.19^+0.21_-0.17 M⊙ and m_2=1.26^+0.10_-0.08 M⊙ . For a well-motivated BNS system where the lighter NS has a mass similar to the mass of non-recycled NSs in MW BNS systems, we find m_1=2.03^+0.15_-0.14 M⊙ and m 2 = 1.35 ± 0.09 M⊙, corresponding to only 7 per cent mass uncertainties. For all scenarios, we expect a prompt collapse of the resulting remnant to a BH. Examining detailed models with component masses similar to our best-fitting results, we find the EM counterpart to GW190425 is expected to be significantly redder and fainter than that of GW170817. We find that almost all reported search observations were too shallow to detect the expected counterpart to GW190425. If the LIGO–Virgo Collaboration promptly provides the chirp mass, the astronomical community can adapt their observations to improve the likelihood of detecting a counterpart for similarly 'high-mass' BNS systems.